Lateral Flow Immunoassay for the Detection of Panton-Valentine Leukocidin in Staphylococcus aureus From Skin and Soft Tissue Infections in the United Arab Emirates - Senok, Abiola; Monecke, Stefan; Nassar, Rania; Celiloglu, Handan; Thyagarajan, Sreeraj; Müller, Elke; Ehricht, Ralf (Frontiers in Cellular and Infection Microbiology, 2021)
Introduction Panton Valentine leukocidin (PVL) is a virulence factor which is associated with methicillin sensitive and resistant Staphylococcus aureus (MSSA/MRSA) causing skin and soft tissue infections (SSTI). This study aimed to evaluate a novel lateral flow immunoassay (LFI) for PVL detection in S. aureus cultures and to describe their genotypic characterization. Methods The study was carried out from January-August 2020 in Dubai, United Arab Emirates. S. aureus isolates associated with SSTI were tested for PVL detection using LFI. DNA microarray-based assays were used for molecular characterization including detection of pvl genes. Results One-hundred thirty-five patients with a clinical diagnosis of SSTIs were recruited. Sixty-six patients received antibiotics, mostly beta lactams (n=36) and topical fusidic acid (n=15). One-hundred twenty-nine isolates (MRSA: n=43; MSSA: n=86) were tested by LFI and DNA microarrays. All 76 (58.9%) isolates which were unambiguously negative for the PVL in LFI were negative for pvl genes using the DNA microarray. All the LFI PVL positive isolates (n=53) had pvl genes detected. This translates into 100% each for sensitivity, specificity, positive and negative predictive values for the LFI. The LFI typically takes about 15 min inclusive of a 10 min incubation period. Predominant S. aureus clonal complexes (CC) were CC30 (n=18), CC22 (n=13), CC5 (n=12), CC1 (n=11), CC152 (n=8), CC15 (n=7); CC97 (n=7); CC8 and CC20 (n=6 each). Among MRSA, the proportion of pvl-positives (35/43; 81%) was higher than among MSSA (n/N=18/86; 21%). The fusidic acid resistance gene fusC was detected in 14 MRSA (33%) compared to 8 MSSA (9%). A co-carriage of fusC and pvl genes was present in 7 MRSA and in one MSSA. Conclusion LFI shows excellent diagnostic accuracy indices for rapid identification of PVL in MSSA/MRSA in a setting with high prevalence of pvl+ve strains. The high occurrence of pvl and fusC genes in MRSA strains causing SSTI is of concern and needs constant surveillance.